Potret Konflik Sosial di Kabupaten Kuantan Singingi Tahun 2013 - Auradian Marta (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2014)
This research is motivated by the social conflict in the Kuantan Singingi Regency high impact on the surrounding environment. The aim of this study determines the source of conflict and effort of handling conflicts in the Kuantan Singingi Regency. The method used in this study is to use a qualitative approach and using the techniques of data collection through interviews, documentation and observation studies. The results showed that the source of conflict in Kuantan Singingi Regency sourced from the economic interests of each actor and conflict resolution is done by consensus and law enforcement